2011
DOI: 10.1501/egifak_0000001223
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the creative thinking levels and the critical thinking disposition of pre-service elementary teachers

Abstract: ABSTRACT. The purpose of the study is to investigate the creative thinking levels and the critical thinking disposition of freshman students at the Division of Elementary Teaching in terms of various variables and to determine whether there is a relationship between the creative thinking levels and the disposition of critical thinking of the students. The study is a descriptive study. In the collection, analysis and interpretation of the data related to the study, quantitative research method was used. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 3 publications
3
11
1
3
Order By: Relevance
“…Findings of a large number of studies conducted with in-service teachers or preservice teachers (e.g. Bakır, 2015;Coşkun, 2013;Coskun & Altinkurt, 2016;Fırat Durdukoca & Arıbaş, 2010;Gök & Erdoğan, 2011;Koçak, et al 2015;Kuvaç & Koç, 2014;Şen, 2009;Tural & Seçgin, 2012;), are consistent with the findings of the current study. A relatively smaller amount of research found that teachers' critical thinking dispositions vary significantly depending on gender.…”
Section: Edupij • Volume 6 • Issue 2 • 2017supporting
confidence: 89%
“…Findings of a large number of studies conducted with in-service teachers or preservice teachers (e.g. Bakır, 2015;Coşkun, 2013;Coskun & Altinkurt, 2016;Fırat Durdukoca & Arıbaş, 2010;Gök & Erdoğan, 2011;Koçak, et al 2015;Kuvaç & Koç, 2014;Şen, 2009;Tural & Seçgin, 2012;), are consistent with the findings of the current study. A relatively smaller amount of research found that teachers' critical thinking dispositions vary significantly depending on gender.…”
Section: Edupij • Volume 6 • Issue 2 • 2017supporting
confidence: 89%
“…As to the studies focusing on critical thinking and problem solving skills, it is clear that the latter are limited in number. On the other hand, the above-mentioned studies have mainly worked on two separate sample groups; 1) in-service and pre-service teachers from different branches (Berkant & Eren, 2013;Gök & Erdoğan, 2011;Kahyaoğlu, 2013;Küçük & Uzun, 2013;McBride, Xiang, & Wittenburg, 2002;Otacıoğlu, 2008;Schreglmann & Doğruluk, 2012;Serin, 2013;Yüksel, Uzun, & Dost, 2013); 2) students attending the department of nursing (Beşer & Kıssal, 2009;Drennan, 2010;Kanbay, et al, 2013;Kawashima & Shiomi, 2007;Shin, Lee, Ha, & Kim, 2006;Şahiner, Açıkgöz, & Açıkel, 2013). As to the samples of the studies, it is seen that the studies conducted with preservice teachers are many more than the others.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' ownership of professional values does not differ in terms of gender. Several studies in the literature resulted that gender had not influenced critical thinking disposition on the basis of total score (Ay, Padem & Eriş, 2010;Coşkun, 2013;Ekinci, 2009;Gök & Erdoğan, 2011;Kuvaç & Koç, 2014;Şen, 2009;Tural & Seçgin, 2012). In addition to these supportive studies, there are several studies that have reported significant differences in critical thinking disposition as of gender both on the basis of total score (Alkın-Şahin, Tunca & Ulubey, 2013) and of some sub-dimensions (Kuvaç & Koç, 2014;Tümkaya, 2011;Zayif, 2008).…”
Section: Discussionmentioning
confidence: 99%